Chronic Conditions and Psychological Distress in Older Asian Americans: The Mediating Role of Subjective Health Perception. Issue 6 (18th August 2022) - Yoon, Hyunwoo; Kim, Seoyoun; Naseh, Mitra; Huang, Ya-Ching; Jang, Yuri
ABSTRACT: Given the importance of understanding the connection between physical and mental health in old age, the study examined the mediating role of subjective health perception in the relationship between chronic conditions and psychological distress among older Asian Americans. Using data from 533 Asian Americans aged 60 and over in the 2016 Asian American Quality of Life Study, the direct and indirect effect models were tested with multivariate linear regressions and the PROCESS macro. Results show that chronic conditions pose significant risks to psychological distress and that subjective health perception mediates their association. The observed role of subjective health perception as an intervening step between physical and mental health offers implications for gerontological social work research and practice by highlighting the importance of positive self-appraisals for the health and well-being in later years of life.